Il diritto della Chiesa cattolica riguardo alla persona anziana - Puig, Fernando (De senectute, 2023)
Four aspects of the Catholic legal understanding of older persons are reviewed. Two of them are more directly related to canon law: the recognition of the equal capacity of the elderly (along with the provisions on sacramental and legal actions that specifically concern them) and the provisions on the effects of advanced age for the holding of government offices and the consequences for elderly ministers. Two others configure aspects of the Church’s magisterium with legal and social implications: the protection of life in its terminal phase, and the care and enhancement of the elderly in ecclesial life, civil society, and the family.